2008
DOI: 10.1080/13693780701670509
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of glyoxylate cycle genes uponParacoccidioides brasiliensisinternalization by murine macrophages andin vitronutritional stress condition

Abstract: Paracoccidioides brasiliensis, the etiologic agent of paracoccidioidomycosis, is a facultative intracellular human pathogen that can persist within macrophage phagolysosomes, indicating that the fungus has evolved defense mechanisms in order to survive under nutritionally poor environments. The analysis of P. brasiliensis transcriptome revealed several virulence factor orthologs of other microorganisms, including the glyoxylate cycle genes. This cycle allows the utilization of two-carbon (C2) compounds as carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 44 publications
1
42
0
1
Order By: Relevance
“…The activation of the glyoxylate cycle is another important adaptation of many intracellular pathogens to the phagosomal microenvironment (34,35,43). Consistent with those observations, our results showed strong activation of the expression of its two regulatory enzymes, isocitrate lyase (Icl) and malate synthase (Mls), upon interaction of C. neoformans with both amoebae and macrophages.…”
Section: Gene Functional Categories (I) Genes Related To the Transposupporting
confidence: 79%
“…The activation of the glyoxylate cycle is another important adaptation of many intracellular pathogens to the phagosomal microenvironment (34,35,43). Consistent with those observations, our results showed strong activation of the expression of its two regulatory enzymes, isocitrate lyase (Icl) and malate synthase (Mls), upon interaction of C. neoformans with both amoebae and macrophages.…”
Section: Gene Functional Categories (I) Genes Related To the Transposupporting
confidence: 79%
“…In this regard, it has been reported that, upon phagocytosis, there is a shift from fermentative to nonfermentative metabolism in intracellular pathogens, which may use two-carbon compounds from fatty acid degradation for energy production via the glyoxylate cycle (2,13,19,32,33,62). Indeed, the upregulation of genes from the glyoxylate cycle has been reported to occur during the M-to-Y differentiation of P. brasiliensis in culture medium (11,12,17,48) and upon the internalization of P. brasiliensis by murine macrophages (9,70). Additionally, nutritional stress conditions have been observed to influence the expression levels of the glyoxylate cycle-related genes of cultured yeast cells (9).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the upregulation of genes from the glyoxylate cycle has been reported to occur during the M-to-Y differentiation of P. brasiliensis in culture medium (11,12,17,48) and upon the internalization of P. brasiliensis by murine macrophages (9,70). Additionally, nutritional stress conditions have been observed to influence the expression levels of the glyoxylate cycle-related genes of cultured yeast cells (9). In this regard, the upregulation of Pbaox during the first hours of Mto-Y differentiation and during the exponential growth of the yeast form could be associated with fatty acid degradation.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR analysis showed that transcript levels of the ICL and MS genes in this fungus increased following phagocytosis by murine macrophages (Derengowski et al, 2008). Penicillium marneffei is a dimorphic fungus that can cause systemic mycosis in humans.…”
Section: Other Fungal Pathogensmentioning
confidence: 99%